Media Pembelajaran dalam Pandangan Islam - Ahmad Zainuri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
With the upgrading of scientific and technological developments, it is the driving force in the utilization of technology in improving the quality of learning. With the mastery of cutting-edge technology, making the media of learning in the view of Islam, as a tool to reveal more deeply in the deepening of the material that exists in the Qur'an, because after all the existing content in the Qur'an no word runs out, the more excavated will be the wider coverage of comprehensive Qur'anic recitation. Thus, the existence of the media is as a tool to explore the sciences contained in al-quran, as has been taught by the Prophet Muhammad to his companions in conveying a good message concerning the truth or kebathilan, so that people will think what to do and which should be shunned as a prohibition, so that the learning media in Islamic view is very wide to be studied further. Dengan pemutakhirnya perkembangan ilmu pengetahuan dan teknologi menjadikan pendorong dalam pemanfaatan teknologi dalam dalam peningkatan kualitas pembelajaran. Dengan penguasaan teknologi yang mutakhir, menjadikan media pembelajaran dalam pandangan Islam, sebagai alat untuk menguak lebih dalam dalam pendalaman materi yang ada dalam al-Qur’an, karena bagaimanapun kandungan yang ada dalam al-Qur’an tidak ada kata habis, semakin digali akan semakin luas cakupan pembahaal a-Qur’an secara komprehensif. Dengan demikian, keberadaan media adalah sebagai alat bantu untuk mendalami ilmu-ilmu yang terkandung dalam al-qur’an, sebagaimana telah diajarkan oleh Nabi Muhammad kepada para sahabatnya dalam menyampaikan risalah baik yang menyangkut kebenaran ataupun kebathilan, sehingga manusia akan berpikir mana yang harus dilakukan dan mana yang harus dijauhi sebagai larangan, sehingga media pembelajaran dalam pandangan Islam sangat luas untuk dikaji lebih lanjut.